2008
DOI: 10.1111/j.1467-873x.2008.00409.x
|View full text |Cite
|
Sign up to set email alerts
|

Drifters and the Dancing Mad: The Public School Music Curriculum and the Fabrication of Boundaries for Participation

Abstract: Recent reforms in the general music curriculum have, for the most part, failed to lessen the attrition rates of African Americans from public school music programs. In this article I assert that an embodied ideal of cultural nobility, exemplified by Auguste Rodin's famous statue, The Thinker, has unconsciously operated as a template for participation. As a model comportment in the Western musical tradition, The Thinker has a broader relevance insofar as other school subjects emerged from similar cultural ideal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 29 publications
0
3
0
Order By: Relevance
“…The history of promoting racial distinctions of musical worth goes back at least as far as Herbert Spencer who, despite his progressive leanings, offered a classification of music ranging from savage to civilized, correlated along racial and ethnic lines (Spencer, 1857(Spencer, /1966. Ruth Gustafson's (2008) work locates Spencer as only one of many to promote the concept of Whiteness as the musical ideal over the centuries. This same work documented subtle but systemic privileging of Whiteness in elementary general music classrooms in Wisconsin.…”
Section: Race and Identitymentioning
confidence: 99%
“…The history of promoting racial distinctions of musical worth goes back at least as far as Herbert Spencer who, despite his progressive leanings, offered a classification of music ranging from savage to civilized, correlated along racial and ethnic lines (Spencer, 1857(Spencer, /1966. Ruth Gustafson's (2008) work locates Spencer as only one of many to promote the concept of Whiteness as the musical ideal over the centuries. This same work documented subtle but systemic privileging of Whiteness in elementary general music classrooms in Wisconsin.…”
Section: Race and Identitymentioning
confidence: 99%
“…Scholars have argued this relates both to the fact that its practices challenge the dominant narrative of Western musical excellence (Hein, 2018;Williams, 2011), and because it is a Black artform (Koza, 2009;Perry, 2004). Both are said to have contributed to its positioning as a redundant or inferior artistic practice (both culturally and technically) and its subsequent exclusion from musical curriculums (Gustafson, 2008). Nevertheless, as participants in Schloss' (2014) ethnographic study showed, to become a respected beat maker requires years of dedicated learning and skill development, and standards within the community can be uncompromising.…”
mentioning
confidence: 99%
“…As music educators, we cannot overlook the seemingly omnipresent everyday racism, the racial grammar within institutional structures and curricula that continue to discourage and disadvantage students of colour (Koza 2008, Gustafson 2008, nor does acknowledg-6 ing the enormous complexity of the issues absolve us from complicity with the perpetuation of that racial grammar.…”
mentioning
confidence: 99%